Superior Strategy in Benign Tracheal Stenosis Treatment: Surgery or Endoscopy? - Aydogmus, Umit; Kis, Argun; Ugurlu, Erhan; Ozturk, Gokhan (The Thoracic and Cardiovascular Surgeon, 2020)
Introduction Due to the variations in (laryngeal) tracheal stenosis (TS) patient groups, there is still no consensus on which patient should be treated with endoscopy or surgery. The aim of the present study was to generate an algorithm in the light of the related literature and the data obtained from a clinic where both endoscopic and surgical treatments are conducted.Method A retrospective analysis was performed on the data of a total of 56 patients during 2013 to 2019. A total of 38 patients were subject to surgery with 31 as a first treatment option and 7 due to the unsatisfactory results of endoscopic treatments. Endoscopic approaches were tried on a total of 29 patients with 25 as initial treatment and 4 due to postsurgical recurrence.Results Symptomatic full control ratio was determined as 69% with endoscopic treatments, 89.5% in subglottic stenosis (SGS) surgery (n = 19), and 89.5% in trachea surgery (n = 19). However, success rates with no recurrence were determined, respectively, as 40.0, 36.4, and 36.4% for patients subject to dilatation, stent, or T tube treatment. Dilatation was observed to be successful in patients with stenotic segment lengths of less than 1.5 cm (p = 0.02). Failure rates increased in SGS (p = 0.03) and TS (p = 0.12) in the surgical group with increasing stenotic segment length. The presence of comorbidities was not effective on treatment success.Conclusion Endoscopic methods are preferred in cases of web-like stenosis. Surgical methods should first be considered for other patients and endoscopic methods should be used on patients who are not suited for surgery or in cases of postsurgical recurrence.
Keywords: trachea; restenosis; endobronchial treatment